Modeling and optimization of lipase-catalyzed synthesis of dilauryl adipate ester by response surface methodology - Abdul Rahman, Mohd Basyaruddin; Chaibakhsh, Naz; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Md Radzi, Salina (Society of Chemical Industry, 2008)
BACKGROUND: Adipate esters are used as low-temperature and low-viscosity plasticizers for polyvinyl chloride and its copolymers. In this work, optimization of lipase-catalyzed production of dilauryl adipate was carried out using response surface methodology (RSM) based on a four-factor-five-level central composite rotatable design (CCRD). Immobilized lipase from Candida antarctica (Novozym 435) was used as catalyst in this reaction. Various reaction parameters affecting the synthesis of adipate ester, including alcohol/acidmolar ratio, amount of enzyme, temperature and reaction time, were investigated.